Strategies to improve the nutritional status of adults and the elderly in Primary Health Care: Systematic review (Research, Society and Development, 2022)
Objective: The objective of this article was to identify strategies adopted to improve the nutritional status of mature adults and the elderly assisted in Primary Health Care (PHC). Methods: This is a systematic literature review, conducted with the PRISMA recommendations, in PubMed, Embase, Web of Science, Science Direct and ACM Digital Library databases. Studies with: participants aged 50 years or older (mature adults and elderly) and description of some type of nutritional strategy applied in PHC were included. Literature and/or protocol review articles, abstracts, case reports, conference presentations, editorials and expert opinions were excluded. Results: In total, 1747 articles were returned for the first analysis, leaving 7 articles that met the eligibility criteria. These used intervention measures such as feeding tips, physical activity, nutritional supplementation and cognitive training. As a result, the need to assess the individuality of each population is evident when implementing a nutritional strategy in PHC. Conclusion: Strategies of an interdisciplinary nature, including more than one practice, seem to be efficient and present greater benefits for mature adults and the elderly, contributing to improve the nutritional status and health conditions of this population.